Effect of interactions of three growth-promoting microorganisms on VAM colonization, spore density, plant growth and nutrient accumulation in tomato (lycopersicon esculentum) seedlings - Thomson T., Edathil; S., Manian; K., Udaiyan (Universiti Putra Malaysia Press, 1995)
Interactions of Azospirillum brasilense and Bacillus megaterium var. phosphaticum and Glomus fasciculatum in the rhizosphere of tomato plants were studied. There was no significant difference in plant growth parameters between YAM-inoculated treatments. Plants inoculated with the phosphobacteria had significantly higher shoot length, which was equivalent to VAM and other VAM + phosphobacteria combinations. Azospirullum or phosphobacteria alone increased plant biomass compared with the uninoculated control. VAM index was significantly reduced with the addition of phosphobacteria. There was no difference in tissue nutrient concentrations between treatments.